THE EFFECT OF JOB SECTORS ON ANXIETY: AN EXPLORATORY STUDY AMONG LOW INCOME MUSLIM FAMILY DURING MCO COVID-19 - Nur Yani Che Hussin ,; Raja Nurul Hafizah Raja Ismail, (Journal of Islamic, Social, Economics and Development, 2021)
Coronavirus or known as COVID-19 has impacted worldwide and has been declaredas a pandemic in 2020. Because of this, there are many mental health cases that arise due toCOVID-19 pandemic such as increases in depression symptoms, anxiety and stress thataffected to all people regardless of their age. Anxiety also happens because of the fear arisesas the number of COVID-19 cases increasing, the loss of job, also changes in educationalsystem and so on. Anxiety is a state of mind marked by tense emotions, nervous thoughts, andphysical changes such as elevated blood pressure. Due to this, this study is to examine the levelof anxiety level among B40 or low-income Muslim family during Movement Control Order(MCO) during COVID-19 pandemic. The study consists of 128 Muslim respondents fromPahang State which focuses on B40 households and the data collected based on DASS-21questionnaire online form. As a result, 16 % had severe, and 68 % had extremely severeanxiety. From the data, it shows that among B40 84% of respondents faced severe andextremely severe anxiety during the pandemic. From the result, it is advisable to increase thesample size for more significant value